A HISTORICAL STUDY OF THE LEGACY OF UTPALA DYNASTY IN KASHMIR, WITH SPECIAL REFERENCE TO AVANTIVERMAN (855-883 A.D.) - Shabir Ahmad Lone (CV. RADJA PUBLIKA, 2025)
Jammu and Kashmir, often referred to as